Periparturient changes in intake, rumen capacity, and selected blood metabolites in beef cows - T.A. Stanley; R.C. Cochran; D.L. Harmon; E.S. Vanzant (Kansas Agricultural Experiment Station Research Reports, 1991)
Four, ruminally cannulated, Hereford x Angus cows were used to study factors associated with feed intake patterns around parturition. Feed intake during the final trimester of gestation was relatively stable, in spite of a noticeable decrease in ruminal capacity. Postpartum feed intake appeared to increase, as did ruminal capacity. Blood progesterone fell after parturition, whereas estradiol did not change except for a large rise around parturition. Some plasma metabolites measured differed before and after calving; however, magnitude and patterns of change do not suggest a direct relationship with intake.
Keywords: Cattlemen' s Day; 1991; Kansas Agricultural Experiment Station contribution; no. 91-355-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 623; Beef; Feed intake; Ruminal capacity; Gestation